Development of a short version of the Aging Males' Symptoms scale: Mokken scaling analysis and Rasch analysis. (2nd April 2016) - Lee, Chin-Pang; Chen, Yu; Jiang, Kun-Hao; Chu, Chun-Lin; Chiu, Yu-Wen; Chen, Jiun-Liang; Chen, Ching-Yen
Abstract: The aim of this study was to develop a psychometrically sound short version of the 17-item Aging Males' Symptoms (AMS) scale using Mokken scale analysis (MSA) and Rasch analysis. We recruited a convenient sample of 1787 men (age: mean (SD) = 43.8 (11.5) years) who visited a men's health polyclinic in Taiwan and completed the AMS scale. The scale was first assessed using MSA. The remaining items were assessed using Rasch analysis. We used a stepwise approach to remove items with χ 2 item statistics and mean square values while monitoring unidimensionality. The item reduction process resulted in a 6-item version of the AMS scale (AMS-6). The AMS-6 scale included a 5-item psychosomatic subscale (original items 1, 4, 5, 8, and 9) and a 1-item sexual subscale (original item 16). Analyses confirmed that the 5-item psychosomatic subscale was a Rasch scale. The AMS-6 correlated well with the AMS scales: the 5-item psychosomatic subscale correlated with the AMS scale ( r between 0.50 and 0.92); the 1-item sexual subscale correlated with the sexual subscale of the AMS scale ( r = 0.81). A 6-item short form of the AMS scale had satisfactory measurement properties. This version may be useful for estimating psychosomatic and sexual symptoms as well as health-related quality of life with a minimal burden on respondents.